What is the role of the research ethics committee? Paternalism, inducements, and harm in research ethics - Garrard, E. (Journal of medical ethics, 2005)
In a recent paper Edwards, Kirchin, and Huxtable have argued that research ethics committees (RECs) are often wrongfully paternalistic in their approach to medical research. They argue that it should be left to competent potential research subjects to make judgments about the acceptability of harms and benefits relating to research, and that this is not a legitimate role for any REC. They allow an exception to their overall antipaternalism, however, in that they think RECs should have the power to prohibit the use of financial inducements to recruit research subjects into trials. In this paper it is argued that these claims are unjustified and implausible. A sketch is provided of an alternative model of the role of the REC as an expert body making judgments about the acceptability of research proposals through a consensual weighing of different moral considerations.